A stereological study of synapse number in the epileptic human hippocampus - Lidia eAlonso-Nanclares; Lidia eAlonso-Nanclares; Lidia eAlonso-Nanclares; Asta eKastanauskaite; Asta eKastanauskaite; Asta eKastanauskaite; José-Rodrigo eRodriguez; José-Rodrigo eRodriguez; José-Rodrigo eRodriguez; Juncal eGonzalez-Soriano; Javier eDeFelipe; Javier eDeFelipe; et al. (Frontiers Media S.A., 2011)
Hippocampal sclerosis is the most frequent pathology encountered in resected mesial temporal structures from patients with intractable temporal lobe epilepsy (TLE). Here, we have used stereological methods to compare the overall density of synapses and neurons between non-sclerotic and sclerotic hippocampal tissue obtained by surgical resection from patients with TLE. Specifically, we examined the possible changes in the subiculum and CA1, regions that seem to be critical for the development and/or maintenance of seizures in these patients. We found a remarkable decrease in synaptic and neuronal density in the sclerotic CA1, and while the subiculum from the sclerotic hippocampus did not display changes in synaptic density, the neuronal density was higher. Since the subiculum from the sclerotic hippocampus displays a significant increase in neuronal density, as well as a various other neurochemical changes, we propose that the apparently normal subiculum from the sclerotic hippocampus suffers profound alterations in neuronal circuits at both the molecular and synaptic level that are likely to be critical for the development or maintenance of seizure activity.